Improving Student Learning Outcomes in Odd Semester Integrated Science Lessons in Class VIII-7 Free Learning Curriculum Using Lectures Plus Demonstration and Exercise Methods at UPT SPF SMP Negeri 2 Sunggal 2022/2023 Academic Year) - Johny Johannes (Journal of Educational Analytics, 2022)
This study aims to find out how to improve student learning outcomes at UPT SPF SMP Negeri 2 Sunggal through the lecture method plus demonstrations and exercises in Integrated Science lessons. This study uses a quantitative approach. The subjects in this study were students in class VIII-7 at UPT SPF SMP Negeri 2 Sunggal for the 2022/2023 academic year, which consisted of 31 students. The data collection technique was carried out using the percentage of individual absorption and classical mastery, as well as by observing the teacher about the implementation of learning through the use of the lecture method plus demonstrations and exercises as well as observing students. The results of this study indicate that the application of the lecture method plus demonstrations and exercises in class can improve learning outcomes in learning the structure and function of food material. This can be seen from the results of the student learning outcomes obtained from cycle I and cycle II, namely: 19% and 69%.